2006
DOI: 10.1007/s10499-006-9060-3
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of 12 microalgae for possible use in aquaculture feed

Abstract: Twelve algal strains representing the classes Cyanophyceae, Prymnesiophyceae, Bacillariophyceae, Rhodophyceae, Cryptophyceae, Chlorophyceae, Xantophyceae and Eustigmatophyceae were selected mainly from the culture collection of the Norwegian Institute for Water Research (NIVA). The algae were grown as continuous cultures in a 1.8 l. reactor, internally illuminated with an 11 W fluorescent tube. The retention time was adjusted in the range 2-4 days to fit the growth rate of the algae. The growth responses and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
201
5
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(237 citation statements)
references
References 25 publications
19
201
5
12
Order By: Relevance
“…Although many studies have demonstrated accumulation of (neutral) lipids in starved cultures of microalgae, relatively little was known about the effect of growth phase on EPA and DHA accumulation. Our study confirms previous results that the absolute amounts of EPA and DHA, but also the total fatty acid content varies considerably between species (Volkman et al 1989;Viso and Marty 1993;Tonon et al 2002;Mansour et al 2005;Patil et al 2007;Boelen et al 2013). Consequently, high interspecific variability in their nutritional value exists.…”
Section: Discussionsupporting
confidence: 91%
“…Although many studies have demonstrated accumulation of (neutral) lipids in starved cultures of microalgae, relatively little was known about the effect of growth phase on EPA and DHA accumulation. Our study confirms previous results that the absolute amounts of EPA and DHA, but also the total fatty acid content varies considerably between species (Volkman et al 1989;Viso and Marty 1993;Tonon et al 2002;Mansour et al 2005;Patil et al 2007;Boelen et al 2013). Consequently, high interspecific variability in their nutritional value exists.…”
Section: Discussionsupporting
confidence: 91%
“…Among them, polyunsaturated fatty acids (PUFAs) especially eicosapentaenoic (EPA), docosahexaenoic (DHA), and arachidonic acids (AA) are the most valuable to create significant physiological and biochemical changes in a body, including reducing risk of cardiovascular diseases [5][6][7][8][9] . Definitely, the total lipid content may vary noticeably among individual species or strains within and between taxonomic groups 7 . In recent years, species of green algae are often considered as a source of essential fatty acids that is necessary not only for improving the organism nutrition, but also for production of biodiesel [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…They are known as the primary producers of a variety of long-chain polyunsaturated fatty acids (PUFAs) in aquatic environments and numerous studies have shown that nutraceutically important omega-3 (ω3) and omega-6 (ω6) PUFAs are quite abundant in microalgae (Otleş and Pire 2001, Bigogno et al 2002, Ikawa 2004, Patil et al 2007, Khozin-Goldberg et al 2011. As the global ω3 and ω6 PUFAs market is expanding at a remarkable rate, microalgae have gained considerable attention as an alternative source to fish oil due to their fast growth rate and high PUFA contents (Seto et al 1984, Benemann et al 1987.…”
Section: Introductionmentioning
confidence: 99%